Anti-carbon deposition catalyst for preparing o-cresol and 2, 6-xylenol

Through the use of Fe/V/Zr/In catalysts, the problem of low conversion and selectivity in the phenol gas-phase methylation reaction in the prior art is solved, and the effects of high conversion, high selectivity and long catalyst life are achieved.

CN119701983APending Publication Date: 2025-03-28SHANGHAI ZHONGHUA TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411929052.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art In the phenol vapor phase methylation reaction, the o-cresol is low when the phenol conversion rate is high, the conversion rate is low when the selectivity is high, the overall yield is low and the catalyst life is short. The main reason is the coking of phenolic compounds and the decomposition of methanol.

Method used

A Fe/V/Zr/In catalyst is provided, prepared by co-precipitation method. The molar ratio of iron, vanadium, zirconium and indium in the catalyst is 100:(2-15):(1-6):(0.2-4). The catalyst has high activity, low carbon deposits and long life.

Benefits of technology

While ensuring high phenol conversion, the yields of o-cresol and 2,6-dicresol are improved, the selectivity of o-cresol (up to more than 50%) is improved, and the life of the catalyst is significantly extended, with a one-way life of up to 5,700 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701983A_ABST
    Figure CN119701983A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and particularly relates to a catalyst, a preparation method thereof and a method for preparing o-cresol and 2, 6-xylenol by using the catalyst. The molar ratio of the iron element to the vanadium element to the zirconium element to the indium element in the catalyst is 100: (2-15): (1-6): (0.2-4), the preparation process is simple, and the raw material cost is low. The catalyst provided by the invention has the characteristics of high conversion rate, high ortho-cresol selectivity and high stability in the reaction of preparing ortho-cresol and 2, 6-xylenol through phenol methylation, the phenol conversion rate can reach 90% or above, the ortho-cresol selectivity can reach 50% or above, and the one-way life of the catalyst exceeds 5700 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a catalyst, a preparation method thereof and a method for preparing o-cresol and 2,6-dimethylphenol by using the catalyst. Background Art

[0002] The ortho-methylation products of phenol include o-cresol and 2,6-dimethylphenol, both of which are important fine chemical intermediates. o-Cresol is an intermediate for the synthesis of pesticides, medicines, resins, spices, antioxidants and other products. o-Cresol can be used in the synthesis of o-cresol phenolic resin, o-cresol phenolic epoxy resin, phenoxycarboxylic acid herbicides (MCPA, MCPB, etc.), and can also be used to produce o-hydroxybenzaldehyde, dyes, spices and antioxidants, and the market demand is very large. 2,6-Dimethylphenol is an important monomer and engineering plastic improver for the synthesis of polyphenylene ether heat-resistant resins, and is also a synthetic raw material for some important pharmaceutical intermediates.

[0003] At present, the main method for synthesizing o-cresol is the gas phase alkylation of phenol and methanol. After the phenol and methanol are gasified, they pass through a catalyst to generate o-cresol, while 2,6-dimethylphenol and a small amount of 2,4,6-trimethylphenol are produced as by-products. General Motors of the United States first used magnesium oxide as a catalyst and achieved industrialization. Later, other companies successively developed Fe 2 O 3 Catalyst, MnO 2 Catalyst, V 2 O 5 Catalyst and Cr 2 O 3 Catalysts, etc. Among them, MnO 2 MgO series catalysts are high temperature catalysts with a reaction temperature of 400℃-500℃ and a short catalyst life; Fe 2 O 3 Series catalyst, Cr 2 O 3 The series of catalysts are medium-temperature type, with the advantages of high activity and low reaction temperature.

[0004] Patent application CN102824916A uses Fe-Mg-Sb catalyst, and the evaluation conditions are phenol:methanol:water molar ratio = 1:3:1, space velocity 1h -1 , with N 2 As carrier gas, at normal pressure, reaction temperature of 320-350℃, the catalyst life reaches 2000 hours, the average conversion rate of phenol is 44.5%, the selectivity of o-cresol is 90.96%, and the selectivity of xylenol is 8.46%. Although the catalyst life reaches 2000 hours, the catalyst activity is still low.

[0005] Patent application CN101514144A uses Fe-Mg-Ce catalyst, and the evaluation conditions are phenol: xylenol: methanol: water = 34:10:38:18 (wt%), and the space velocity is 1.2h -1 , and at normal pressure, N 2 As carrier gas, when the reaction temperature is 280-450℃, the catalyst life can reach 500 hours, the average conversion rate of phenol is 33.4%, and the selectivity of o-cresol is 96%. Although the selectivity of o-cresol is high, the conversion rate of phenol is not high, the catalyst activity is low, and xylenol needs to be added to the reactants.

[0006] From the above analysis, it is found that the gas-phase methylation reaction of phenol has problems such as low selectivity of o-cresol when the conversion rate is high, low conversion rate of phenol when the o-cresol selectivity is high, low overall yield of o-cresol, and short life. Ogawa Tsuyoshi et al. found that the main cause of catalyst deactivation is coking of phenolic compounds and carbon deposition of methanol decomposition. Wang Xiaoguang et al. in China also studied the deactivation mechanism of the catalyst, and the results showed that catalyst deactivation is mainly caused by carbon deposition. Summary of the invention

[0007] The present invention aims at the above problems existing in the prior art, and provides a carbon deposition resistant composite oxide catalyst and a preparation method thereof, as well as a method for preparing o-cresol and 2,6-dimethylphenol using the composite oxide catalyst of the present invention. The present invention can obtain high yields of o-cresol and 2,6-dimethylphenol while ensuring a high phenol conversion rate, and can improve the selectivity of o-cresol (for example, to more than 50%).

[0008] Specifically, one aspect of the present invention provides a Fe / V / Zr / In catalyst, which contains iron, vanadium, zirconium and indium, and the molar ratio of iron, vanadium, zirconium and indium is 100:(2-15):(1-6):(0.2-4).

[0009] In one or more embodiments, the Fe / V / Zr / In catalyst has a molecular formula of Fe a V b Zr c In d O, where 0<a<1, 0<b<1, 0<c<1, 0<d<1, a:b:c:d=100:(2-15):(1-6):(0.2-4), 3a+5b+4c+3d=2.

[0010] In the present invention, the molecular formula Fe can be calculated based on the valence states of Fe, V, Zr, In, and O in the catalyst, which are +3, +5, +4, +3, and -2, respectively, and the molar ratio of the four metal elements Fe, V, Zr, and In.a V b Zr c In d The values ​​of a, b, c, and d in O.

[0011] In some embodiments, a is 0.4-0.7, e.g., 0.4, 0.45, 0.5, 0.52, 0.55, 0.56, 0.58, 0.59, 0.6, 0.62, 0.65, 0.7.

[0012] In some embodiments, b is 0.01-0.07, for example, 0.01, 0.015, 0.017, 0.02, 0.025, 0.03, 0.033, 0.035, 0.04, 0.045, 0.047, 0.05, 0.055, 0.058, 0.06, 0.065, 0.07.

[0013] In some embodiments, c is 0.005-0.05, for example, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.012, 0.014, 0.016, 0.017, 0.018, 0.02, 0.025, 0.029, 0.03, 0.035, 0.04, 0.05.

[0014] In some embodiments, d is 0.0005-0.05, for example, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.0012, 0.0014, 0.0016, 0.0018, 0.002, 0.0025, 0.003, 0.0032, 0.0033, 0.0 0.04, 0.0045, 0.005, 0.0055, 0.006, 0.0064, 0.0065, 0.007, 0.0075, 0.008, 0.0085, 0.009, 0.0095, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05.

[0015] Another aspect of the present invention provides a method for preparing the Fe / V / Zr / In catalyst described in any embodiment of the present invention, the method comprising: dissolving an iron source, a vanadium source, a zirconium source and an indium source in water, adding a precipitant dropwise for co-precipitation, and obtaining a Fe / V / Zr / In catalyst after post-treatment.

[0016] In one or more embodiments, the molar ratio of the iron element in the iron source to the vanadium element in the vanadium source is 100:(2-15).

[0017] In one or more embodiments, the molar ratio of the iron element in the iron source to the zirconium element in the zirconium source is 100:(1-6).

[0018] In one or more embodiments, the molar ratio of the iron element in the iron source to the indium element in the indium source is 100:(0.2-4).

[0019] In one or more embodiments, the iron source is selected from one or more of ferric nitrate, ferric chloride, and ferric sulfate.

[0020] In one or more embodiments, the vanadium source is selected from one or more of ammonium metavanadate, vanadium oxalate, and ammonium vanadate.

[0021] In one or more embodiments, the zirconium source is selected from one or more of zirconium nitrate, zirconium oxychloride, and zirconium chloride.

[0022] In one or more embodiments, the indium source is selected from one or more of indium chloride or indium nitrate.

[0023] In one or more embodiments, the precipitating agent is aqueous ammonia.

[0024] In one or more embodiments, the post-treatment comprises the following steps:

[0025] The coprecipitate is aged, dried for the first time, and then pulverized. The pulverized product is washed, dried for the second time, and calcined.

[0026] In one or more embodiments, the aging time is 1-5 hours.

[0027] In one or more embodiments, the first drying is carried out at a temperature of 80-150° C. and for a drying time of 6-12 hours.

[0028] In one or more embodiments, the second drying temperature is 80-120° C., and the drying time is 6-12 hours.

[0029] In one or more embodiments, the calcination temperature is 350° C.-600° C., and the calcination time is 2-6 hours.

[0030] Another aspect of the present invention provides a method for preparing o-cresol and 2,6-dimethylphenol, the method comprising: contacting a material containing phenol and methanol with the Fe / V / Zr / In catalyst described in any embodiment of the present invention or the Fe / V / Zr / In catalyst prepared by the method described in any embodiment of the present invention, so that phenol undergoes a methylation reaction.

[0031] In one or more embodiments, in the material containing phenol and methanol, the molar ratio of phenol to methanol is 1:(3-5).

[0032] In one or more embodiments, the temperature of the reaction is 300°C to 400°C.

[0033] In one or more embodiments, the reaction space velocity is 0.8-1.2h -1 .

[0034] In one or more embodiments, the reaction pressure is 0.1 MPa-0.5 MPa.

[0035] The method adopts a multi-component coprecipitation method, which is more convenient and easy to scale up; the catalyst prepared by the method has a unique composition ratio, high catalyst activity, less carbon deposition, and long service life. The catalyst of the present invention has the characteristics of high conversion rate, high ortho-cresol selectivity and high stability in the reaction of phenol methylation to prepare ortho-cresol and 2,6-dimethylphenol, with a phenol conversion rate of more than 90%, an ortho-cresol selectivity of more than 50%, less carbon deposition, and strong anti-carbon deposition ability. The one-way life can reach 5700 hours. After the catalyst runs for 5700 hours, the phenol conversion rate is still maintained at more than 90%, and the ortho-cresol selectivity is maintained at more than 50%. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a thermogravimetric (TG) graph of the catalyst in Example 3 of the present invention after TOS (material-catalyst contact reaction time) is 1000 h under experimental condition 1.

[0037] Figure 2 This is the TG graph of the catalyst in Example 3 of the present invention after the TOS time is 5700h under experimental condition 1.

[0038] Figure 3 This is the TG graph of the catalyst in Comparative Example 2 of the present invention after the TOS time is 1000h under experimental condition 1.

[0039] Figure 4 This is the TG graph of the catalyst in Comparative Example 2 of the present invention after the TOS time is 5700h under experimental condition 1. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.

[0041] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0042] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0043] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0044] Herein, the sum of the percentages of the various components of the composition is 100%.

[0045] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined by the present invention.

[0046] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0047] Herein, o-cresol refers to o-methylphenol; 2,6-dimethylphenol refers to 2,6-dimethylphenol.

[0048] In the Fe / V / Zr / In catalyst of the present invention, the molar ratio of iron to vanadium is 100:(2-15), for example, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14.

[0049] In the Fe / V / Zr / In catalyst of the present invention, the molar ratio of iron element to zirconium element is 100:(1-6), for example, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5.

[0050] In the Fe / V / Zr / In catalyst of the present invention, the molar ratio of iron element to indium element is 100:(0.2-4), for example, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5.

[0051] The Fe / V / Zr / In catalyst of the present invention can be prepared by the following method: dissolving an iron source, a vanadium source, a zirconium source and an indium source in water, dropping a precipitant for co-precipitation, and obtaining a Fe / V / Zr / In catalyst after post-treatment; the iron source is preferably one or more of ferric nitrate, ferric chloride or ferric sulfate, the vanadium source is preferably one or more of ammonium metavanadate, vanadium oxalate or ammonium vanadate; the zirconium source is preferably one or more of zirconium nitrate, zirconium oxychloride or zirconium chloride; and the indium source is preferably one or more of indium chloride or indium nitrate.

[0052] The molar ratio of the iron element in the iron source to the vanadium element in the vanadium source can be 100:(2-15), for example, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14.

[0053] The molar ratio of the iron element in the iron source to the zirconium element in the zirconium source can be 100:(1-6), for example, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5.

[0054] The molar ratio of the iron element in the iron source to the indium element in the indium source can be 100:(0.2-4), for example, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5.

[0055] The post-treatment preferably comprises the following steps: aging the coprecipitate, drying it for the first time, and then pulverizing it; washing the pulverized product, drying it for the second time, and calcining it.

[0056] The aging time is preferably 1-5 hours, for example 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h.

[0057] The temperature of the first drying is preferably 80-150° C., such as 90° C., 100° C., 110° C., 120° C., 130° C., 140° C. The time of the first drying is preferably 6-12 hours, such as 7h, 8h, 9h, 10h, 11h.

[0058] The temperature of the second drying is preferably 80-120° C., such as 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C. The time of the second drying is preferably 6-12 hours, such as 7h, 8h, 9h, 10h, 11h.

[0059] When the coprecipitate is pulverized after the first drying, it is preferred to pulverize the coprecipitate to 60-80 mesh, such as 65 mesh, 70 mesh, or 75 mesh.

[0060] The calcination temperature is preferably 350° C.-600° C., for example 360° C., 370° C., 380° C., 390° C., 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., 460° C., 470° C., 480° C., 490° C., 500° C., 510° C., 520° C., 530° C., 540° C., 550° C., 560° C., 570° C., 580° C., 590° C. The calcination time is preferably 2-6 hours, for example 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h.

[0061] The Fe / V / Zr / In catalyst of the present invention can be used to prepare o-cresol and 2,6-dimethylphenol in the phenol-methanol gas phase method, and the specific steps are to take the Fe / V / Zr / In catalyst and load it into a reactor, introduce a mixed gas of phenol and methanol, and react at high temperature. In the process of preparing o-cresol and 2,6-dimethylphenol in the phenol-methanol gas phase method, the reaction products are mainly o-cresol and 2,6-dimethylphenol, and a small amount of by-products such as p-cresol, 2,4,6-trimethylphenol, etc. are generated.

[0062] When the Fe / V / Zr / In catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the molar ratio of phenol to methanol can be 1:(3-5), such as 1:3.5, 1:4, or 1:4.5.

[0063] When the Fe / V / Zr / In catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the introduction space velocity of phenol and methanol is preferably 0.8-1.2 h -1 , for example 0.9h -1 , 1h -1 , 1.1h -1 .

[0064] When the Fe / V / Zr / In catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the reaction temperature is preferably 300°C-400°C, for example, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, more preferably 335°C-380°C.

[0065] When the Fe / V / Zr / In catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the reaction pressure is preferably 0.1 MPa-0.5 MPa, for example, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa.

[0066] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0067] In the present invention, the molecular formula of the catalyst is calculated based on the molar ratio of iron, vanadium, zirconium and indium in the raw materials, and the valence states of the iron, vanadium, zirconium and indium in the catalyst are +3, +5, +4 and +3 respectively.

[0068] In the present invention, the calculation formula of the conversion rate of phenol is: phenol conversion rate = molar amount of converted phenol / total molar amount of phenol before reaction × 100%;

[0069] In the present invention, the calculation formula of the selectivity of o-cresol is: o-cresol selectivity = molar amount of o-cresol generated by the reaction / molar amount of phenol converted × 100%;

[0070] In the present invention, the calculation formula of the selectivity of 2,6-xylenol is: 2,6-xylenol selectivity = molar amount of 2,6-xylenol generated by the reaction / molar amount of phenol converted × 100%.

[0071] The present invention detects the amount of carbon deposits on the catalyst by thermogravimetric analysis, thereby reflecting the catalyst's ability to resist carbon deposits. During the catalytic reaction, the catalyst will deposit carbon as the reaction time increases, reducing its activity and causing the conversion rate of phenol to show a downward trend.

[0072] The thermogravimetric analysis method in the present invention uses a NETZSCH TG 209F3 thermal analyzer to perform thermogravimetric analysis on the catalyst. The test uses an air atmosphere, a temperature range of 40°C-800°C, and a heating rate of 10°C / min. The specific test details refer to JY / T0589.1-2020 General Rules for Thermal Analysis Methods Part 1: General Rules and JY / T 0589.4-2020 General Rules for Thermal Analysis Methods Part 4: Thermogravimetric Method. The smaller the value of TG%, the better the anti-carbon deposition ability.

[0073] Example 1

[0074] 121g of ferric nitrate nonahydrate, 0.98g of ammonium metavanadate, 3.60g of zirconium nitrate pentahydrate and 0.16g of hydrated indium chloride were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 2 hours, filtered and dried at 100°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 6 hours, and calcined at 400°C for 5 hours to obtain a product with the molecular formula of Fe 0.62 V 0.017 Zr 0.017 In 0.0014 Fe / V / Zr / In catalyst for O.

[0075] Example 2

[0076] 121g of ferric nitrate nonahydrate, 1.97g of ammonium metavanadate, 3.60g of zirconium nitrate pentahydrate and 0.40g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 5 hours, filtered and dried at 120°C for 6 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 100°C for 12 hours, and calcined at 490°C for 2 hours to obtain a product with the molecular formula of Fe 0.59 V 0.033 Zr 0.016 In 0.0033 Fe / V / Zr / In catalyst for O.

[0077] Example 3

[0078] 121g of ferric nitrate nonahydrate, 1.97g of ammonium metavanadate, 3.60g of zirconium nitrate pentahydrate and 0.79g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 3 hours, filtered and dried at 100°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 100°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.58 V 0.033 Zr 0.016 In 0.0064Fe / V / Zr / In catalyst for O.

[0079] Example 4

[0080] 121g of ferric nitrate nonahydrate, 2.91g of ammonium metavanadate, 3.60g of zirconium nitrate pentahydrate and 0.40g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 4 hours, filtered and dried at 120°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 410°C for 6 hours to obtain a product with the molecular formula of Fe 0.56 V 0.047 Zr 0.016 In 0.0032 Fe / V / Zr / In catalyst for O.

[0081] Example 5

[0082] 121g of ferric nitrate nonahydrate, 3.90g of ammonium metavanadate, 7.21g of zirconium nitrate pentahydrate and 2.00g of hydrated indium chloride were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and the mixture was aged at room temperature for 5 hours, filtered and dried at 80°C for 12 hours, and then crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.52 V 0.058 Zr 0.029 In 0.015 Fe / V / Zr / In catalyst for O.

[0083] Comparative Example 1

[0084] 12.12 g of ferric nitrate nonahydrate and 3.51 g of ammonium metavanadate were dissolved in 150 g of methanol, 18.45 g of zirconium oxide powder was added to the above solution, the reaction system was heated to 70°C, and the mixture was evaporated while stirring until there was no water, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.07 V 0.07 Zr 0.36 O catalyst.

[0085] Comparative Example 2

[0086] 121g of ferric nitrate nonahydrate, 1.97g of ammonium metavanadate and 3.60g of zirconium nitrate pentahydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 3 hours, filtered and dried at 120°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe0.59 V 0.033 Zr 0.017 O catalyst.

[0087] Comparative Example 3

[0088] 121g of ferric nitrate nonahydrate, 1.97g of ammonium metavanadate, 3.60g of zirconium nitrate pentahydrate and 4.02g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 3 hours, filtered and dried at 120°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.56 V 0.032 Zr 0.016 In 0.032 O catalyst.

[0089] Comparative Example 4

[0090] 121g of ferric nitrate nonahydrate, 5.86g of ammonium metavanadate, 0.72g of zirconium nitrate pentahydrate and 0.79g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 3 hours, filtered and dried at 120°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 380°C for 3 hours to obtain a product with the molecular formula of Fe 0.51 V 0.086 Zr 0.0029 In 0.0057 O catalyst.

[0091] Comparative Example 5

[0092] 121g of ferric nitrate nonahydrate, 0.39g of ammonium metavanadate, 11.46g of zirconium nitrate pentahydrate and 0.79g of indium chloride hydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation, and aged at room temperature for 3 hours, filtered and dried at 120°C for 12 hours, and crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 510°C for 3 hours to obtain a product with the molecular formula of Fe 0.58 V 0.0064 Zr 0.052 In 0.0064 O catalyst.

[0093] Test Case

[0094] 1. Performance evaluation experiment of catalyst in o-cresol synthesis

[0095] In the following experimental process, the catalyst was sieved to obtain particles with a mesh size of 12-20 and then filled into the reactor. TOS is the contact time between the catalyst and the material, that is, the catalyst reaction time.

[0096] Experimental condition 1:

[0097] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. 5 g of the catalyst of 12-20 mesh prepared by Comparative Examples 1-5 and Examples 1-5 were respectively filled in, so that the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 350°C, phenol and methanol were prepared into a reaction liquid in a molar ratio of 1:5, and a metering pump was used to pass the reaction liquid into the gasifier for gasification and then into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 1.2 h -1 After TOS was 1000h, the product was cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity, and 2,6-dimethylphenol selectivity data are shown in Table 1. The catalyst was subjected to thermogravimetric analysis, and the test results are shown in Table 1.

[0098] Table 1: Performance of catalysts in o-cresol synthesis under experimental condition 1

[0099]

[0100] Experimental condition 2:

[0101] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. 5 g of the catalysts of 12-20 mesh prepared by Comparative Examples 1-5 and Examples 1-5 were respectively filled in, and the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 380°C, phenol and methanol were prepared into a reaction liquid in a molar ratio of 1:3, and a metering pump was used to pass the reaction liquid into the gasifier for gasification and then into the reactor. The reaction pressure was set to 0.1 MPa and the reaction space velocity was 0.8 h -1 After TOS was 1000h, the product was cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity, and 2,6-dimethylphenol selectivity data are shown in Table 2. The catalyst was subjected to thermogravimetric analysis, and the test results are shown in Table 2.

[0102] Table 2: Performance of catalysts in o-cresol synthesis under experimental condition 2

[0103]

[0104] It can be seen from Table 1 and Table 2 that the reaction of preparing o-cresol using the Fe / V / Zr / In catalyst of the present invention has a high phenol conversion rate and a high o-cresol selectivity, with the phenol conversion rate reaching more than 90% and the o-cresol selectivity reaching more than 50%.

[0105] It can be seen from the experimental results of Examples 1-5 and Comparative Example 1 that when the Fe content in the catalyst is too little, the V and Zr contents are too much, and the In element is not contained, so that the molar ratio of iron, vanadium, zirconium and indium does not satisfy 100:(2-15):(1-6):(0.2-4), the phenol conversion rate and o-cresol selectivity of the reaction are low.

[0106] It can be seen from the experimental results of Examples 1-5 and Comparative Example 2 that when the catalyst lacks the In element, the TG% value of the catalyst will become higher, indicating that adding an appropriate amount of In element to the catalyst can effectively improve the catalyst's ability to resist carbon deposition, thereby increasing the life of the catalyst.

[0107] It can be seen from the experimental results of Examples 1-5 and Comparative Example 3 that when the In element content in the catalyst is too high, so that the molar ratio of iron element, vanadium element, zirconium element and indium element does not meet 100:(2-15):(1-6):(0.2-4), the selectivity of o-cresol in the reaction will decrease.

[0108] It can be seen from the experimental results of Examples 1-5 and Comparative Example 4 that when the V element content in the catalyst is too high and the Zr element content is too low, so that the molar ratio of iron element, vanadium element, zirconium element and indium element does not meet 100:(2-15):(1-6):(0.2-4), the phenol conversion rate and o-cresol selectivity of the reaction will decrease.

[0109] It can be seen from the experimental results of Examples 1-5 and Comparative Example 5 that when the V element content in the catalyst is too little and the Zr element content is too much, so that the molar ratio of iron element, vanadium element, zirconium element and indium element does not meet 100:(2-15):(1-6):(0.2-4), the phenol conversion rate and o-cresol selectivity of the reaction will decrease.

[0110] In summary, only when the catalyst contains iron, vanadium, zirconium and indium, and the molar ratio of iron, vanadium, zirconium and indium satisfies 100:(2-15):(1-6):(0.2-4), can the reaction simultaneously achieve high phenol conversion rate, high o-cresol selectivity and low TG%.

[0111] 2. Performance evaluation experiment of catalyst in o-cresol synthesis under different TOS durations

[0112] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. The Fe / V / Zr / In catalyst prepared in Example 3 was sieved to obtain particles of 12-20 mesh, which were then filled into the reactor so that the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 350°C, phenol and methanol were mixed into a reaction liquid in a molar ratio of 1:5, and a metering pump was used to pass the reaction liquid into the gasifier for gasification and then into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 1.2 h -1 , respectively contacted with Fe / V / Zr / In catalyst for reaction, TOS was 1000h, 2000h, 3000h, 4200h, 5000h, 5700h, the product was cooled and collected for gas chromatography offline analysis, and the corresponding phenol conversion rate, o-cresol selectivity and 2,6-dimethylphenol selectivity data are shown in Table 3; the catalyst was subjected to thermogravimetric analysis, and the test results are shown in Table 3.

[0113] Figure 1 and Figure 2 They are TG graphs of the catalyst in Example 3 of the present invention after TOS time of 1000h or 5700h under experimental condition 1.

[0114] Table 3: Performance of the catalyst in Example 3 at different TOS times in o-cresol synthesis

[0115]

[0116] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. The catalyst prepared in Comparative Example 2 was sieved to obtain particles of 12-20 mesh, which were then filled into the reactor so that the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 350°C, phenol and methanol were mixed into a reaction liquid in a molar ratio of 1:5, and a metering pump was used to pass the reaction liquid into the gasifier for gasification and then into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 1.2 h -1 After being in contact with the catalyst for 1000h, 2000h, 3000h, 4200h and 5000h, the products were cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity and 2,6-dimethylphenol selectivity data are shown in Table 4. The catalyst was subjected to thermogravimetric analysis, and the test results are shown in Table 4.

[0117] Figure 3 and Figure 4 They are TG graphs of the catalyst in Comparative Example 2 of the present invention after TOS time of 1000h or 5000h under experimental condition 1.

[0118] Table 4: Performance of the catalyst in Comparative Example 2 at different TOS times in o-cresol synthesis

[0119]

[0120] It can be seen from Tables 3 and 4 that the life of the Fe / V / Zr / In catalyst of the present invention is as long as 5700 hours. During the whole process, a high phenol conversion rate (greater than 90%) and an o-cresol selectivity of more than 50% are maintained, which is longer than the catalyst in Comparative Example 2.

Claims

1. A Fe / V / Zr / In catalyst, characterized in that: The Fe / V / Zr / In catalyst contains iron, vanadium, zirconium and indium, and the molar ratio of the iron, vanadium, zirconium and indium is 100:(2-15):(1-6):(0.2-4).

2. The Fe / V / Zr / In catalyst according to claim 1, characterized in that The molecular formula of the Fe / V / Zr / In catalyst is Fe a V b Zr c In d O, where a:b:c:d=100:(2-15):(1-6):(0.2-4).

3. A method for preparing the Fe / V / Zr / In catalyst according to claim 1 or 2, characterized in that: The method comprises: dissolving an iron source, a vanadium source, a zirconium source and an indium source in water, dropping a precipitant for co-precipitation, and obtaining a Fe / V / Zr / In catalyst after post-treatment.

4. The method according to claim 3, characterized in that The method has one or more of the following features: The molar ratio of the iron element in the iron source to the vanadium element in the vanadium source is 100:(2-15); The molar ratio of the iron element in the iron source to the zirconium element in the zirconium source is 100:(1-6); The molar ratio of the iron element in the iron source to the indium element in the indium source is 100:(0.2-4); The iron source is selected from one or more of ferric nitrate, ferric chloride and ferric sulfate; The vanadium source is selected from one or more of ammonium metavanadate, vanadium oxalate and ammonium vanadate; The zirconium source is selected from one or more of zirconium nitrate, zirconium oxychloride and zirconium chloride; The indium source is selected from one or more of indium chloride or indium nitrate; The precipitant is aqueous ammonia.

5. The method according to claim 3, characterized in that The post-processing comprises the following steps: The coprecipitate is aged, dried for the first time, and then pulverized. The pulverized product is washed, dried for the second time, and calcined.

6. The method according to claim 5, characterized in that The method has one or more of the following characteristics: The aging time is 1-5 hours; The first drying temperature is 80-150°C and the drying time is 6-12 hours; The second drying temperature is 80-120°C and the drying time is 6-12 hours; The calcination temperature is 350° C.-600° C., and the calcination time is 2-6 hours.

7. A method for preparing o-cresol and 2,6-dimethylphenol, characterized in that: The method comprises: contacting a material containing phenol and methanol with the Fe / V / Zr / In catalyst according to claim 1 or 2 or the Fe / V / Zr / In catalyst prepared by the method according to any one of claims 3 to 6, so that phenol undergoes a methylation reaction.

8. The method according to claim 7, characterized in that The method has one or more of the following features: In the material containing phenol and methanol, the molar ratio of phenol to methanol is 1:(3-5); The reaction temperature is 300°C-400°C; The reaction space velocity is 0.8-1.2h -1 ; The reaction pressure is 0.1 MPa-0.5 MPa.

Citation Information

Patent Citations

  • Method for preparing o-cresol

    CN101514144A

  • Phenol o-methylated catalyst and its preparation method

    CN102824916A